Factors Related to Work Accidents Cases in Nurse at dr. Ben Mboy Hospital, Ruteng - Noorce Christiani Berek; Theresia S. Dali; Dominirsep O. Dodo (Lontar : Journal of Community Health, 2020)
The hospital is a complex health service institution that needs to implement worker health and safety efforts. Work accidents often experienced by nurses are needlestick injuries. This study aimed to determine the factors associated with work accidents, including knowledge, attitudes, actions, K3RS information, and K3RS supervision of nurses in the inpatient room of BLUD RSU dr. Ben Mboi Ruteng in 2019. This research is quantitative research with a cross-sectional study design. The research population was nurses in the inpatient room. The sample size was 113 nurses taken by simple random sampling. The data analysis used was Chi-square with α = 0,05 (5%). The results showed that the majority of nurses were aged 30-50 years old (80,5%), D3 education level (85,8%), and tenure of 10-20 years (47,8%). Variables related to work accidents on nurses were K3RS information (p-value = 0.008), and K3RS supervision (p-value = 0.028), while knowledge (p-value = 0.170), attitude (p-value = 1,000), and actions (p-value = 0.075) were not related to work accidents. Regular training and supervision are vital to prevent workplace accidents for nurses.